Psychosocial and mental health challenges facing perinatally HIV-infected adolescents along the Kenyan coast: a qualitative inquiry using the socioecological model - Stanley W. Wanjala; Stanley W. Wanjala; Moses K. Nyongesa; Moses K. Nyongesa; Stanley Luchters; Stanley Luchters; Stanley Luchters; Amina Abubakar; Amina Abubakar; Amina Abubakar; Amina Abubakar (Frontiers Media S.A., 2024)
BackgroundThe advent of antiretroviral therapy has led perinatally HIV-infected (PHI) adolescents to live long, fulfilling lives through lifelong treatment. However, there is limited knowledge about the lived experiences and psychosocial and mental health challenges faced by PHI adolescents in sub-Saharan Africa, where 80% of PHI adolescents reside. To address this gap, we adapted the socioecological model to investigate the challenges and lived experiences of PHI adolescents in rural coastal Kenya.MethodsBetween October and November 2018, a sample of 40 participants (20 PHI adolescents and their 20 primary caregivers) participated in a qualitative study using an H-assessment data collection approach for adolescents and focus group discussions with caregivers. Data analysis was conducted using a framework approach on NVIVO 11 software.ResultsPHI adolescents from this setting experience many challenges across various levels of the ecosystem. At the individual level, challenges include living in denial, HIV status disclosure, antiretroviral adherence, internalized stigma, and mental health issues. Within the family, challenges such as parental loss, insufficient care from parents, and unacceptance lead to threats of harm. In the broader community, key challenges such as gossip, unsupportive community members, long waiting times at the health facility, isolation, rejection, and an unresponsive school system fail to address the needs of PHI adolescents. Finally, HIV-related stigma and discrimination manifested across different levels of the socioecological framework. To cope with these challenges, PHI adolescents often rely on privacy and social support from their families.ConclusionThe findings underscore the need to develop and implement multi-level adolescent-friendly interventions to address PHI adolescent challenges and guide future investment in adolescent's health. Furthermore, there is a need to address internalized and interpersonal stigmas through individual-level interventions that promote resilience and the active involvement of adolescents, their caregivers, peers, and teachers who are their social support system.